On the politicization of intergovernmental fiscal relations in Germany after unification - Friedrich Schneider; Hans Pitlik; Harald Strotmann; Günther Schmid (Johannes Kepler University of Linz, Department of Economics, 2001)
A recent decision of the German Constitutional Court requires political decision makers to revise the system of intergovernmental transfers in order to limit free bargaining among state and federal government officials. The present paper provides empirical support for the thesis that political discretion has become increasingly important in the transfer negotiations after Unification. We attempt to show why political influences gained weight relative to economic considerations in the determination of net gains. This politicization of the fiscal transfer system appears to be a consequence of the inability of policy makers to agree on a fundamental reform in the early 1990's.
Keywords: D7; H77; 330; Horizontaler Finanzausgleich; Verfassungsgericht; Deutschland